Sensory Quality of Fresh Noodles with Pandan Leaf Extract as a Natural Colorant - Nisa Yusnia; Rahmi Holinesti; Wiwik Gusnita; Riski Gusri Utami (Darul Yasin Al Sys, 2026)
Fresh noodles are widely consumed food products; however, their production commonly involves synthetic additives, including artificial colorants, which may pose potential health risks. Therefore, natural ingredients are needed as safer alternatives, one of which is pandan leaf extract, known for its natural green color and distinctive aroma. This study aimed to analyze the effect of pandan leaf extract substitution on the sensory quality of fresh noodles, including color, aroma, texture, resistance to breakage, and taste. An experimental method was applied using two treatments: 150 mL of water as the control treatment (X₁) and 150 mL of pandan leaf extract as the substitution treatment (X₂). Organoleptic evaluation was conducted by 30 panelists using a sensory assessment scale covering color, aroma, texture, and taste attributes. The collected data were analyzed using a pooled variance t-test, also referred to as an independent samples t-test, with SPSS version 22. The findings indicate that pandan leaf extract substitution had a significant effect on all sensory attributes of fresh noodles. Treatment X₂ obtained the highest mean scores across all assessed parameters, including color (5.36; light green), aroma (5.70; highly fragrant), chewy texture (5.17), resistance to breakage (5.00), and taste (5.04; savory). These results demonstrate that pandan leaf extract can improve the sensory quality of fresh noodles while functioning as a natural colorant and aroma-enhancing ingredient. The study concludes that substituting 150 mL of pandan leaf extract produces better overall sensory quality in fresh noodles and may support the development of food products using natural ingredients.